Effect of Ketamine versus Dexmedetomidine on Postoperative Delirium after Coronary Artery Bypass Grafting CABG - علي, غاندي; نجوى رقماني , (Latakia University Journal -Medical Sciences Series, 2024)
Background and Objective: Delirium is bad complication especially after major surgeries such as Coronary Artery Bypass Grafting Surgery (CABG). Recent studies has shown that Dexmedetomidine and Ketamine could decrease Delirium. This study compared between the effectiveness of the two drugs on the Delirium and after (CABG). Methods and Materials: In this study (150) patients underwent (CABG) at Al-Assad Universal Hospital in Damascus between 2020-2021. They were divided randomly into three groups: Dexmedetomidine (D) group, Ketamine (K) group and control (C) group. Then we used a table to write the number of patients developed Delirium in the intensive care unit (ICU), after that we compared between the three groups to determine the difference between them. Conclusion: comparing the occurance of Delirium showed that There was no statistically significant difference between the three groups, p-value=0.6.